PENGARUH HARGA PRODUK DAN FAKTOR BUDAYA TERHADAP MINAT BELI MASYARAKAT PADA PASAR BARU KECAMATAN KENCONG JEMBER - Muhammad Syarofi; Rusmini Rusmini; Halimatus Sa’diyah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Traditional markets are a place for products of basic community needs produced by economic actors that occur, small or even micro events, most of which are products from agriculture or plantations. Currently, modern shops are also increasing, coupled with the increasing trend of public spending, not all products produced from agriculture can be sold in modern shops, therefore traditional markets become a means of selling products that have been produced by farmers. Humans have several needs in life, one of which is the need for the market as a means of support in meeting their daily needs. This study aims to empirically examine product price variables and cultural factors that influence people's buying interest in Pasar Baru, Kencong District. This study uses a quantitative research approach with the type of survey research. Sampling used the Nonrobability Sampling technique which was Incidental Sampling, where the research sample was all people who had shopped at Pasar Baru Kencong twice or more, determining the number of samples using the Lemeshow formula collecting 100 respondents. Collecting data using a questionnaire method with a Likert Scale research instrument. Data analysis with validity and reliability tests, data testing with t test (partial), F test (simultaneous), R2 test (coefficient of determination) and multiple linear regression with the help of the Statistical Package for the Sciences (SPSS) software version 16. This study concludes that product prices have a significant effect on people's buying interest in Pasar Baru, Kencong District with a t-test value of 0.011 <0.05 and a t-count value of 2.589 > ttable 1.980. The results of the t-test also show that cultural factors have a significant effect on people's buying interest with a significant value of 0.000 <0.05 and a tcount value of 4.041 <ttable 1.980. The results of the F test show that product prices and cultural factors simultaneously have a significant effect on people's buying interest with a significant value of 0.000 0.05 with an Fcount value of 27.957 > Ftable 3.11.